Un incontro lusofono plurale di lingue, letterature, storie, culture - Graziani, Michela (Studi e saggi, 2018)
The volume Un incontro lusofono plurale di lingue, letterature, storie, culture (A plural Lusophone encounter of languages, literatures, stories, cultures) aims at highlighting one of the specificities of the Lusophone culture: the linguistic-literary pluralism that continues to distinguish Portuguese culture, from Brazil, to Africa and Asia, since the time of maritime discoveries. The collected essays mark, in this regard, a twofold path: they are intercultural, since they alternate the literary and linguistic aspects from the humanistic to the contemporary era, but they also are intergeneris as they alternate not only historiography and treatises with poetry and narrative - with inter-artistic incursions across literature, painting and photography - but also linguistic aspects, namely grammatical, and examples of rewritings and translational questions, in a sort of further Lusophone dialogue between genres and topoi.